2018
DOI: 10.1186/s12893-018-0381-8
|View full text |Cite
|
Sign up to set email alerts
|

Is pneumatic balloon dilation safe and effective primary modality of treatment for post-sleeve gastrectomy strictures? A retrospective study

Abstract: BackgroundThe optimal treatment of sleeve strictures has not been agreed upon at the current time. At our institution, we began using pneumatic balloon dilation to help resolve these obstructions in 2010. Herein we report our experience with pneumatic balloon dilation for the treatment of sleeve strictures.MethodsFrom Jan 2010 to Dec 2016 we retrospectively reviewed our prospectively kept database for patients who developed a Laparoscopic Sleeve Gastrectomy (LSG) stricture within 90 days of surgery. If the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 24 publications
1
22
0
6
Order By: Relevance
“…Sin embargo, no hubo diferencias significativas entre estas dos cirugías cuando se compararon parámetros nutricionales, tales como vitamina D, B1, B12, calcio, albúmina sérica, proteínas séricas totales, y parámetros metabólicos como glicemia en ayuno, hemoglobina glicosilada, insulina basal, y perfil lipídico 19 . Recientemente Zaveri et al, publicaron una serie de 437 pacientes que se sometieron a SIPS 20 . A los 4 años de seguimiento, los pacientes tuvieron un promedio de %PEP de 86%.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Sin embargo, no hubo diferencias significativas entre estas dos cirugías cuando se compararon parámetros nutricionales, tales como vitamina D, B1, B12, calcio, albúmina sérica, proteínas séricas totales, y parámetros metabólicos como glicemia en ayuno, hemoglobina glicosilada, insulina basal, y perfil lipídico 19 . Recientemente Zaveri et al, publicaron una serie de 437 pacientes que se sometieron a SIPS 20 . A los 4 años de seguimiento, los pacientes tuvieron un promedio de %PEP de 86%.…”
Section: Resultsunclassified
“…Ocho pacientes desarrollaron complicaciones relacionadas con el largo del asa eferente (7 con diarrea, 1 hipoproteinemia), por lo tanto, se requirió alargamiento de dicho segmento del intestino delgado. La remisión de DM, dislipidemia, hipertensión arterial, y apnea del sueño, a los 4 años de seguimiento, fue 81,3, 70,5, 71, y 64%, respectivamente 20 .…”
Section: Resultsunclassified
“…Logically, a more rigid balloon with a larger diameter would be more likely to tear the stenotic tissue in the stricture zone, yielding a higher success rate. 8,25,26 Additionally, an increased duration time of 15 to 20 minutes per dilation using the larger balloon in the initial attempt could better overcome the elasticity of the fibrosis that occurs in these stricture sites, thus leading to higher success rates as in the case of Dhorepatil et al 26 Although anecdotal evidence from various dual-balloon studies may suggest superiority of the achalasia balloon, the type of balloon used may ultimately depend on accessibility and length of stenosis of SGS. For instance, although Shnell et al 21 reported higher success with the achalasia balloon, they were unable to position the larger balloon appropriately in the distal SGS cases because of limited access of the introducer in a twisted SGS.…”
Section: Discussionmentioning
confidence: 99%
“…En el caso de las estenosis post gVt, la tasa de éxito va desde 44% a 100% 71,72 y pueden ser manejadas con dilatación con balón o posicionamiento de stents. La tabla 3 67,[71][72][73][74][75][76][77][78][79] resume las series publicadas para el manejo de las estenosis post gVt y sus resultados.…”
Section: Dilatación Endoscópica Con Balón Y Stentsunclassified